Sunscreens: Time to think beyond UV rays - Chitralekha Keisham; Nelson Elangbam; Rashmi Sarkar (Wolters Kluwer Medknow Publications, 2018)
It has been known to us that solar radiation contributes to photoaging. Until recently, it was thought to be due to ultraviolet rays alone. However, a growing number of evidence confirms that visible and infrared (IR) rays also contribute to extrinsic aging. Visible and IR rays account for 50% and 45% of the solar radiation reaching the earth. Ultraviolet A induces retrograde mitochondrial signal, thus leading to induction of matrix metalloproteinase. Ultraviolet B and IRC cause heat-related generation of free radicals and destruction of collagen and elastin. Exposure to visible light induces cytokines, free-radical formation, and pigmentary changes in human skin. The end result of solar radiation is generation of free radicals and ultimately oxidative damage, photoaging, and photocarcinogenesis. The present broad spectrum sunscreen does not provide complete protection of the human skin from oxidative insult. So, a combination of a sun protection factor active component along with an antioxidant is the ideal way of photoprotection. Till date, a number of antioxidants have been tried in human and animals which have shown to be an effective photoprotective agent, though few studies have failed to prove the same. Even with conflicting reports, effect of antioxidants on human skin needs to be explored more. A good study design with a large sample size in humans must be conducted as visible light and IR rays contribute significantly to photodamage.